2012
DOI: 10.1158/1078-0432.ccr-12-0827
|View full text |Cite
|
Sign up to set email alerts
|

Genetically Defined Subsets of Human Pancreatic Cancer Show Unique In Vitro Chemosensitivity

Abstract: Purpose Pancreatic cancer (PC) is the fourth cause of death from cancer in the western world. Majority of patients present with advanced unresectable disease responding poorly to most chemotherapeutic agents. Chemotherapy for PC might be improved by adjusting it to individual genetic profiles. We attempt to identify genetic predictors of chemosensitivity to broad classes of anticancer drugs. Experimental Design Using a panel of genetically defined human PC cell lines, we tested gemcitabine (anti-metabolite),… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(45 citation statements)
references
References 48 publications
0
45
0
Order By: Relevance
“…Several reports documenting gemcitabine sensitivity of PDA cell lines show higher induction of apoptosis following chemotherapeutic treatment than prior to treatment, but these studies involve cells treated for 48 to 72 h and seeded at densities ranging from 5 to 15 times lower than in the present study (77)(78)(79). As our study was concerned with the ability of influenza virus to induce apoptosis following infection at a high MOI, we chose to study the response over a period of 24 h, starting with those of confluent monolayers, to monitor CPE following infection.…”
Section: Discussionmentioning
confidence: 71%
“…Several reports documenting gemcitabine sensitivity of PDA cell lines show higher induction of apoptosis following chemotherapeutic treatment than prior to treatment, but these studies involve cells treated for 48 to 72 h and seeded at densities ranging from 5 to 15 times lower than in the present study (77)(78)(79). As our study was concerned with the ability of influenza virus to induce apoptosis following infection at a high MOI, we chose to study the response over a period of 24 h, starting with those of confluent monolayers, to monitor CPE following infection.…”
Section: Discussionmentioning
confidence: 71%
“…Cytotoxicity of cisplatin in pancreatic cancer cell lines was positively correlated with MAP4K2 expression, whereas NLRC4 deficiency may lead to radio-resistance of the respective tumor [69, 70]. Similarly p53 dysfunction results in resistance to radiotherapy and chemotherapy, including drugs widely used in ONB like etoposide [71].…”
Section: Genome Sequencingmentioning
confidence: 99%
“…For example, in vitro studies have suggested that genetic testing may even be useful to preselect patients for treatment with chemotherapy agents [61]. Tumors harboring Fanconi anemia pathway gene mutations (such as BRCA1, BRCA2, and PALB2 mutations) and tumors harboring ATM mutations are examples of potential individualized treatment targets.…”
Section: Pancreatic Ductal Adenocarcinomamentioning
confidence: 99%